TECHNOLOGICAL MEASURES FOR ENHANCING THE WEAR RESISTANCE OF PISTON RINGS - PIDHAICHUK, SVITLANA; DROBOT, OLHA; BABAK, OLEH; SYDORENKO, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
High mechanical and operational properties of piston rings are essential for maximizing automobile engine power and ensuring long-term efficient performance. This study proposes technological improvements to enhance the wear resistance of piston rings. A novel method of surface strengthening for gray cast iron rings—based on thermal diffusion alloying combined with thermal cycling—has been developed and tested to increase both wear resistance and durability of the rings and their associated components.The research introduces a surface strengthening technique using a pasty saturating medium and identifies an effective powder mixture for complex diffusion saturation of gray cast irons. The proposed method includes a specific temperature regime for thermodiffusion saturation combined with thermal cycling.Findings reveal that optimal operational properties of gray cast iron piston rings are achieved through thermodiffusion alloying in a powder mixture based on sormite (comprising chamotte, ammonium chloride, and ferrosilicon). The study found that thermal diffusion hardening with thermal cycling reduces the cementation process of sealing rings to 3–4 hours, which is 5–6 times shorter than the traditional method.Moreover, the addition of ferrosilicon to the saturating mixture increases process efficiency by 2–3 times and enhances the antifriction properties of the saturated layer by 8–13 times. The influence of the developed method on key operational properties of the rings was thoroughly investigated, including assessments of manufacturability and reliability. Practical recommendations for industrial implementation of this diffusion hardening method with thermal cycling are provided.
Keywords: piston rings; thermal diffusion alloying; thermal cycling; antifriction properties; gray cast iron; surface hardening